Mechanisms for the regulation of memory B-cell recall responses in mice. (19th July 2021) - Kitamura, Daisuke
Abstract: Upon infection by pathogens or vaccination, the adaptive immune system rapidly but transiently produces antibodies. Some weeks later, however, long-lasting immunity is established that protects the host against the same pathogens almost for life through continuous production of antibodies on one hand and the maintenance of cytotoxic T cells on the other, collectively called immunological memory. The antibody-mediated arm, also called serological memory, is mainly exerted by long-lived plasma cells and memory B cells (MBCs). MBCs express receptors for the specific pathogens and circulate to survey the body for almost a life-long period. Upon recognizing the pathogen, MBCs clonally expand and produce a large amount of the specific antibodies to stop the infection, the process called a (memory) recall response. Although such a function of MBCs has long been known, the mechanism of how their performance is regulated has been obscure. This is due to their paucity in the body, lack of definitive surface markers and obscure ontogeny. However, recent studies have revealed the multifold mechanisms by which the recall response of MBCs is regulated: rapid and enhanced antibody production is due to a mechanism intrinsic to MBCs, namely, up-regulated expression levels of surface molecules interacting with T cells and the property of IgG-class antigen receptors; to a property of the responsible subset of MBCs; and to co-stimulation through innate receptors and cytokines. It has also been unveiled that the recall response is negatively regulated by an inhibitory receptor on MBCs and by antigens with repetitive epitopes.